Study on the Structural Behaviour of the Topside Modules of FPSO under the Forces Exerted on the Ship Hull - M. Saleh; R. Amirabadi; A. Kheiri (Numerical Methods in Civil Engineering)
The extraction of oil and gas from deep water is one of the most important challenges of the oil and gas industry today. FPSO is one of the leading platforms for deep waters. This study discussed the performance of FPSO deck modules under loads exerted on the hull of the ship. Modeling of the studied module was executed by SACS software and the effect of support using neoprene in the function of the module’s members was studied. The members of this module are divided into two general areas: the first area includes fulcrum members under the main deck of module and the second area includes installed members on the main deck and equipment of the module which is investigated in three directions; longitudinal, transverse and vertical. After analysis, it was confirmed that in the module which uses neoprene, the connected members to the neoprene have a significant decrease in relative stress, whereas, the transverse members exhibited increased relative stress. On the other hand, the vertical and longitudinal members displayed insignificant changes.